Developing a circumpolar programme for the monitoring of Arctic terrestrial biodiversity - Christensen, Tom (Ambio, 2020)
The Arctic is undergoing biological and environmental changes, and a coordinated effort to monitor is critical to detect these changes. The Circumpolar Biodiversity Monitoring Programme (CBMP) of the Arctic Council biodiversity working group, Conservation of Arctic Flora and Fauna (CAFF), has developed pan-Arctic biodiversity monitoring plans that aims to improve the ability to detect and report on long-term changes. Whilst introducing this special issue, this paper also presents the making of the terrestrial monitoring plan and discusses how the plan follows the steps required for an adaptive and ecosystem-based monitoring programme. In this article, we discuss how data on key findings can be used to inform circumpolar and global assessments, including the State of the Arctic Terrestrial Biodiversity Report, which will be the first terrestrial assessment made by the CBMP. Key findings, advice for future monitoring and lessons learned will be used in planning next steps of pan-Arctic coordinated monitoring.